PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT ADHI KARYA (PERSERO) TBK PERIODE 2012-2023 - Karmila, Karmila; Mardiana, Sri (JIM : Journal Of International Management, 2025)
This study aims to examine the effect of the Current Ratio and Debt to Equity Ratio on Return on Assets at PT Adhi Karya (Persero) Tbk for the period 2012-2023. This research uses a quantitative method with an associative approach. The sample consists of financial statements, including the balance sheet and income statement, obtained through secondary data. The data analysis techniques used include descriptive statistical analysis, classical assumption tests, multiple linear regression tests, correlation & determination coefficient tests, and hypothesis testing through t-tests and F-tests. The results show that partially, the Current Ratio has a positive and significant effect on Return on Assets, as indicated by the t-value of 5.083 > 2.622 (t-table) with a significance value of 0.001 < 0.05. The Debt to Equity Ratio also has a positive and significant effect on Return on Assets, as shown by the t-value of 3.316 > 2.622 (t-table) with a significance value of 0.009 < 0.05. The simultaneous test shows that both the Current Ratio and Debt to Equity Ratio have a positive and significant effect on Return on Assets. The R-Square value of 0.747 indicates that the Current Ratio and Debt to Equity Ratio simultaneously explain 74.7% of the variation in Return on Assets, while the remaining 25.3% is influenced by variables outside the model.